CTLA-4 Blockade following Relapse of Malignancy after Allogeneic Stem Cell Transplantation is Associated with T cell Activation but not Increased Levels of T Regulatory Cells - Zhou, Jiehua (2010)
Cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4) is a key negative regulator of T cell activation and proliferation. Ipilimumab is a human monoclonal antibody that specifically blocks the binding of CTLA-4 to its ligand. To test the hypothesis that blockade of CTLA-4 by ipilimumab could augment graft-versus-malignancy effects (GVM) without a significant impact on graft-versus-host disease (GVHD), we conducted a phase I clinical trial of ipilimumab infusion in patients with relapsed malignancy following allogeneic hematopoietic stem cell transplant (allo-HSCT). Here we report the analysis of peripheral blood T lymphocyte reconstitution, T regulatory cell (Treg) expression and T cell activation markers after a single dose of ipilimumab in 29 patients. Peripheral blood samples were collected from all patients before and after ipilimumab infusion. We analyzed lymphocyte immunophenotyes, including levels of CD4(+)CD25(high) cells and T cell activation markers in all cases. Levels of CD4(+)CD25(high)Foxp3(+) cells and intracellular CTLA-4 in CD4(+) T cells were also assessed in the last 11 cases. We found that baseline levels of CD4 and CD45RO positive T cells were lower in patients compared to normal controls. More than 50% patients had abnormally low lymphocyte counts, either CD4 or/and CD8 T cells, and some had no circulating B lymphocyte. The percentages of both CD4(+)CD25(high) and CD4(+)CD25(high)Foxp3(+) T cells were significantly higher in patients prior to ipilimumab infusion than in healthy donors. 20 of 29 patients showed an elevated level of CD4(+)CD25(low) activated T cells at baseline while only 3 of 26 healthy donors had such a population of activated T cells. After ipilimumab infusion, both CD4(+) and CD8(+) T lymphocyte counts significantly increased. There was no consistent change in absolute lymphocyte count, or in T cells expressing the activation marker CD69. However, CD4(+)CD25(low) T cells in 20 of 29 patients, and CD4(+)HLA-DR(+) T cell in the last 10 patients increased in the first 60 days following ipilimumab infusion. Although the percentages of both CD4(+)CD25(high) and CD4(+)CD25(high)Foxp3(+) T cells significantly decreased during the observation period, the absolute cell counts did not change. Intracellular CTLA-4 expression in CD4(+) CD25(lo/−) T cells significantly increased after ipilimumab infusion. We conclude that CTLA-4 blockade by a single infusion of ipilimumab increased CD4(+) and CD4(+)HLA-DR(+) T lymphocyte counts and intracellular CTLA-4 expression at the highest dose level. There was no significant change in Treg cell numbers after ipilimumab infusion. These data show that significant changes in T cell populations occur upon exposure to a single dose of ipilimumab. Further studies with multiple doses are needed to explore this phenomenon further and to correlate changes in lymphocyte subpopulations with clinical events.